Developing Children's Number Sense Using Calculators - Hamzah Hamzah; Abdul Rahman (Universitas Negeri Malang, 2016)
In the past, most people believed that calculators were useful only for obtaining or checking answers to computation problems. Therefore, in many ways they have often been ignored as a teaching resource. Based on the lack of interest, some parents and teachers have shied away from calculator's use, especially in primary mathematics. Many researchers have also found that using calculators as a teaching aid is most useful and effective in developing number sense and mental computation. The Calculator-Aware Number (CAN) project in Britain found that children develop their own strategies for carrying out calculations and achieve a high level of numeracy when using calculators